2021
DOI: 10.3390/applmicrobiol1010007
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Using Droplet Digital PCR for Environmental Samples

Abstract: Droplet digital polymerase chain reaction (ddPCR) is a method used to detect and quantify nucleic acids even when present in exceptionally low numbers. While it has proven to be valuable for clinical studies, it has failed to be widely adopted for environmental studies but despite some limitations, ddPCR may represent a better option than classical qPCR for environmental samples. Due to the complexity of the chemical and biological composition of environmental samples, protocols tailored to clinical studies ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…The stronger ddPCR signal reported from the low concentration cell treatments can be attributed to better discrete cloud clustering and therefore higher amplitude level readout in diluted samples (Kokkoris et al, 2021). The negative effect of high target concentration was especially evident in RNA dataset; however, the pattern of membrane performance remained consistent across treatments, suggesting no or limiting impact of that factor on efficiency assessment results.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The stronger ddPCR signal reported from the low concentration cell treatments can be attributed to better discrete cloud clustering and therefore higher amplitude level readout in diluted samples (Kokkoris et al, 2021). The negative effect of high target concentration was especially evident in RNA dataset; however, the pattern of membrane performance remained consistent across treatments, suggesting no or limiting impact of that factor on efficiency assessment results.…”
Section: Discussionmentioning
confidence: 93%
“…This is consistent with results from previous studies, where the influence of dissolved substances in the water column on DNA detection rates has been reported, and explained by PCR inhibition effects (Albers et al, 2013; Hunter et al, 2019) or nucleic acids binding to suspended particles (Stoeckle, Beggel, et al, 2017). The stronger ddPCR signal reported from the low concentration cell treatments can be attributed to better discrete cloud clustering and therefore higher amplitude level readout in diluted samples (Kokkoris et al, 2021). The negative effect of high target concentration was especially evident in RNA dataset; however, the pattern of membrane performance remained consistent across treatments, suggesting no or limiting impact of that factor on efficiency assessment results.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple parameters need to be adjusted, as they could impact the sensitivity of ddPCR. These include the amount of input genetic material, the concentration of the primers used in the reaction, the cycling conditions (e.g., duration of denaturation, annealing, and extension; number of cycles; temperature during annealing and extension), also determining the fluorescence threshold and LOD [ 62 ]. Of interest, a study showed that undigested fragments could fail packaging into droplets, compromising the performance of the assay [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if less likely than RT-qPCR, ddPCR detection ability could also be impacted by inhibitors or non-target genetic material. Thus, optimization of the ddPCR assay and strict quality control measures are needed to achieve accurate and reproducible results [ 58 , 62 ]. Improved artificial intelligence algorithms could also help towards this direction [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to qPCR, ddPCR shows better performance in detecting low concentrations of target genes in environmental samples. Moreover, it has the potential to reduce the effect of qPCR inhibitors, although its application to complex environmental samples needs further optimization [111]. However, qPCR is more reliable in detecting higher concentrations (2 × 10 5 or 2 × 10 4 gene copies/PCR), since ddPCR displays higher variability and less precision in these concentration ranges [112].…”
Section: Pcr-based Methodsmentioning
confidence: 99%